Modulation of Voltage-Gated Calcium Channels by Orphanin FQ in Freshly Dissociated Hippocampal Neurons - Knoflach, Frederic (J Neurosci, 1996)
Orphanin FQ (OFQ) has recently been reported to be an endogenous ligand for the opioid-like LC132 receptor. The effect of OFQ on high voltage-gated calcium channels (VGCCs) was examined in freshly dissociated rat pyramidal neurons using the whole-cell configuration of the patch-clamp technique. High-threshold Ba(2+) currents were reversibly inhibited by OFQ. The depression of the currents was associated with a slowed rate of activation and a change in the activation I–V relationship at step potentials higher than +30 mV. In concentration–response experiments, a mean (±SEM) pEC(50) value of 7.0 ± 0.07 and a Hill coefficient of 1.5 ± 0.08 (n = 5) were obtained. The near-maximum inhibition of the Ba(2+) currents by OFQ (1 μm) amounted to 31 ± 2.2% of control (n = 15). Opioid receptors could not account for the effects of OFQ on VGCCs, because naloxone, a broad spectrum μ-, δ-, and κ-receptor antagonist, did not reduce the effectiveness of OFQ. When GTP-γ-S was included in the pipette, the depression of the currents by OFQ was irreversible, whereas currents from neurons preincubated with pertussis toxin were not inhibited by OFQ, consistent with the involvement of a PTX-sensitive G-protein. When selective blockers of VGCCs were used, it was demonstrated that all subtypes of VGCCs were affected by OFQ. In conclusion, the effect of OFQ on VGCCs expressed in hippocampal CA3 and CA1 neurons may play an important role in the regulation of hippocampal cell excitability and neurotransmitter release.